1996
DOI: 10.1016/s0969-2126(96)00012-3
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic domain of avian sarcoma virus integrase: conformation of the active-site residues in the presence of divalent cations

Abstract: Binding of the required metal ions does not lead to significant structural modifications in the active site of the catalytic domain of ASV IN. This indicates that at least one metal-binding site is preformed in the structure, and suggests that the observed constellation of the acidic residues represents a catalytically competent active site. Only a single divalent cation was observed even at extremely high concentrations of the metals. We conclude that either only one metal ion is needed for catalysis, or that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
133
2
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 164 publications
(146 citation statements)
references
References 32 publications
10
133
2
1
Order By: Relevance
“…Both observed conformations of this side chain appear to be energetically favorable. In the first mode of binding, predominantly observed in the previously reported structures (6,7,9), Asp-64 is anchored by a hydrogen bond to a water molecule, which in turn is stabilized by an additional hydrogen bond with the side chain of Asp-121. Because it was shown previously that this conformation of Asp-64 remains unchanged upon binding of several divalent metal cations, we refer to it as the "active" conformation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Both observed conformations of this side chain appear to be energetically favorable. In the first mode of binding, predominantly observed in the previously reported structures (6,7,9), Asp-64 is anchored by a hydrogen bond to a water molecule, which in turn is stabilized by an additional hydrogen bond with the side chain of Asp-121. Because it was shown previously that this conformation of Asp-64 remains unchanged upon binding of several divalent metal cations, we refer to it as the "active" conformation.…”
Section: Discussionmentioning
confidence: 92%
“…In the previously reported structures of ASV IN (6,7,9), with the sole exception of the low pH complexes with an inhibitor (8), the side chain of Asp-64 points toward the side chain of Asp-121, forming hydrogen bonds mediated by a water molecule (or a metal ion). The difference F o Ϫ F c electron density extending from C␤ of residue 64 unambiguously indicates that the Asx-64 side chain (Asn in the mutant ASVIN64 or Asp in ASVIN5) is rotated by ϳ150°around the C␣OC␤ bond (Fig.…”
Section: Conformation Of Asp/asn-64 -mentioning
confidence: 99%
“…All IN DDE mutants display reduced 3Ј end processing, strand transfer, and disintegration, and mutation of any of these residues in related transposases and polynucleotidyltransferases diminishes their respective activities. Structures have been solved for HIV-1 and avian sarcoma virus (ASV) IN in the absence of DNA (14)(15)(16)(17)30) and for Tn5 transposase with a bound donor end (30). Crystals of the HIV-1 and ASV IN core domains with Mg 2ϩ or Mn 2ϩ contain one metal coordinated by D64 and D116 (site I; positions in HIV-1 IN); however, an additional metal coordinated by D64 and E152 (site II) was observed in ASV IN by using either Zn 2ϩ or Cd 2ϩ (17).…”
Section: Discussionmentioning
confidence: 99%
“…For IN and related enzymes that catalyze phosphoryl transfer reactions, the number of metals present and required in the active site remains controversial. Structural studies of IN reveal a single binding site for Mg 2ϩ or Mn 2ϩ (14)(15)(16), although a second metal has been observed with Zn 2ϩ or Cd 2ϩ (17).…”
mentioning
confidence: 99%
“…This motif is believed to be conserved among all transposases and retroviral integrases. The DDE residues serve to coordinate divalent metal ions that are required for catalysis (11)(12)(13)(14). A previous study has suggested that Asp-97 and Glu-326 contribute to the coordination of one metal ion, whereas Asp-97 and Asp-188 coordinate a second ion (15).…”
Section: Tn5 Transposase (Tnp)mentioning
confidence: 99%